2001
DOI: 10.1523/jneurosci.21-15-05520.2001
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Mossy Fiber Long-Term Potentiation and Associative Learning in Pituitary Adenylate Cyclase Activating Polypeptide Type I Receptor-Deficient Mice

Abstract: The pituitary adenylate cyclase activating polypeptide (PACAP) type I receptor (PAC1) is a G-protein-coupled receptor binding the strongly conserved neuropeptide PACAP with 1000-fold higher affinity than the related peptide vasoactive intestinal peptide. PAC1-mediated signaling has been implicated in neuronal differentiation and synaptic plasticity. To gain further insight into the biological significance of PAC1-mediated signaling in vivo, we generated two different mutant mouse strains, harboring either a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 49 publications
7
136
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23] In accordance with previous observations, 30 in situ hybridization of adult rat brains showed intense expression of PAC 1 mRNA in the periglomerular and granule cells of the olfactory bulb, the granule cells of the dentate gyrus, the cerebral cortex (especially layer II) and many regions of the hypothalamus (Figure 3a and b). Thus, prominent signals for both DBZ and PAC 1 transcripts were detected in the dentate gyrus (Figure 3b upper panels).…”
Section: Effect Of Pacap On Disc1/dbz Interactionsupporting
confidence: 91%
See 3 more Smart Citations
“…[16][17][18][19][20][21][22][23] In accordance with previous observations, 30 in situ hybridization of adult rat brains showed intense expression of PAC 1 mRNA in the periglomerular and granule cells of the olfactory bulb, the granule cells of the dentate gyrus, the cerebral cortex (especially layer II) and many regions of the hypothalamus (Figure 3a and b). Thus, prominent signals for both DBZ and PAC 1 transcripts were detected in the dentate gyrus (Figure 3b upper panels).…”
Section: Effect Of Pacap On Disc1/dbz Interactionsupporting
confidence: 91%
“…DISC1 is a possible candidate gene for schizophrenia that is predominantly expressed in certain brain [18][19][20][21][22][23] was indicated by our present findings. DISC1 has been proposed to be a multifunctional protein that interacts with multiple proteins of the centrosome and cytoskeletal system at distinct domains.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…They found that Rab3A knockout mice present no detectable defect in learning and memory. These data indicate that deficient mossy fiber LTP is probably not the reason for the spatial learning defect of RIM1-alpha mutants, in agreement with other studies in mutant mice lacking Rab3A 169 or with defects in PKA activity Huang et al; 170 see also Villacres et al, 171 Wu et al 172 and Otto et al 173 In order to investigate whether the decrease in Pr could be the cause of the behavioral phenotype, Powell et al included in the analysis synaptotagmin 1 R233Q knockin mice to compare them with RIM1-alpha mutants. Synaptotagmin 1 is a Ca 2 þ sensor for fast and synchronous exocytosis.…”
Section: Rim1-alpha Is Critical For Learning and Memorysupporting
confidence: 89%